Clinical characteristics and prognosis of patients with left ventricular thrombus in East China - Li, Cheng; Lau, Wenjie; Qian, Ningjing; Song, Liuguang; Jin, Chunna; Zhou, Dao; Yu, Yi; Pan, Xiaohong; Zhou, Quan (Frontiers in Cardiovascular Medicine, 2022)
Background: Left ventricular thrombus (LVT) is a serious complication in the patients with left ventricular dysfunction. However, there is still a paucity of data on treatments and prognosis of patients with LVT. This study aims to evaluate the clinical characteristics of patients with LVT and to identify the predictors of clinical outcomes of LVT. Methods: From January 2010 to January 2020, 237 patients diagnosed as LVT were retrospectively included from The Second Affiliated Hospital Zhejiang University School of Medicine in East China. Clinical characteristics, treatments, major adverse cardiovascular events (MACE) and bleeding events (TIMI I&II）were collected. MACE determined as the composite of all-cause mortality, ischemic stroke, acute coronary emboli, acute peripheral artery emboli. Results: The rate of all-cause mortality was 28.3% (89.6% due to cardiovascular death); ischemic stroke 8.4%; acute coronary emboli 3%; peripheral artery emboli 1.7%; bleeding events (TIMI I&II) 7.6% during a median follow-up of 736 days. Total LVT regression occurred in 152 patients (64.1%). Atrial fibrillation (HR, 3.049; 95% CI 1.264-7.355; P = 0.013), Moderate and severe renal function injury (HR, 2.97; 95% CI, 1.027-4.281; P = 0.042), LVEF ≤ 50% (HR, 2.243; 95% CI 1.090-4.615; P = 0.005) were independent risk factors for MACE, while use of β-blocker (HR, 0.397 95% CI 0.210-0.753; P = 0.005) was its protective factor. Age (HR, 1.021; 95% CI 1.002-1.040; p = 0.031), previous CABG (HR, 4.634; 95% CI 2.042-10.517; P = 0.000), LVEF ≤ 50% (HR, 3.714; 95% CI 1.664-8.290; P = 0.001), large thrombus area (HR, 1.071; 95% CI 1.019-1.126; P = 0.007) were independent risk factors for increasing all-cause mortality, while use of β-blocker (HR, 0.410; 95% CI 0.237-0.708; P = 0.001) was protective factor. Conclusions: This study showed atrial fibrillation, moderate and severe renal dysfunction, LVEF ≤ 50% were independent risk factors for MACE; age, previous CABG, LVEF ≤ 50%, large thrombus area were independent risk factors for all-cause mortality. It found out the use of β blockers could improve prognosis for the first time. It is recommended that doctors could be more active in applying LVT patients with anticoagulants.